Effectiveness of an Out-of-Pocket Cost Removal Intervention on Health Check Attendance in Japan - Murayama, Hiroshi (Int J Environ Res Public Health, 2021)
Annual health checks are important for identifying individuals at high risk for cardiometabolic diseases. However, there are socioeconomic disparities in health check attendance rates, and an intervention to lower financial barriers could be useful for increasing health check utilization. In this study, we aimed to evaluate the effectiveness of an out-of-pocket cost removal intervention on health check attendance in Japan. Data were obtained on beneficiaries of the National Health Insurance system of Yokohama City, Kanagawa Prefecture, Japan. In 2018, Yokohama started an intervention to remove out-of-pocket costs for specific health checks for all National Health Insurance beneficiaries. We analyzed data from 2015−2018 (131,295 people aged 40–74 years; 377,660 observations). A generalized estimating equation showed that people were more likely to receive specific health checks in 2018 (after the out-of-pocket cost removal intervention started) than in 2017 (immediately before the intervention; odds ratio [95% confidence interval] = 1.167 [1.149–1.185]), after adjusting for age, gender, tax exemption, and residential area. Stratified analyses revealed that the effectiveness of the out-of-pocket cost removal intervention was greater among the older age group and those who did not receive a tax exemption (i.e., those with relatively higher income). The present study showed that the out-of-pocket cost removal intervention could promote specific health check utilization. This indicates that removing financial barriers could motivate people’s behavior regarding health check attendance.